Dermoscopy in albinism - Mayuri Kalantri; Uday Khopkar; Prachi Gole (Pigment International)
Albinos are at great risk for developing cutaneous malignancy. We report a 33-year-old patient of occulocutaneous albinism who presented with multiple actinic keratoses and basal-cell carcinoma. This report highlights the increase in vascular structures seen on dermoscopy as a clue toward malignant transformation. We hereby emphasize the role of dermoscopy for monitoring and screening of skin tumors in albinism and other genodermatosis prone to skin tumors.